All-aqueous emulsions as miniaturized chemical reactors in the food and bioprocess technology. (June 2020) - Madadlou, Ashkan; Saggiomo, Vittorio; Schroën, Karin; Fogliano, Vincenzo
Highlights: Aqueous two-phase systems can be miniaturized to all-aqueous emulsions. They can be used to accomplish numerous reactions within droplets and on droplets. In-droplet reactions include extractive bioconversion, and microgel synthesis. On-droplet reactions include microcapsule formation and interfacial catalysis. Microfluidics enables control over formation and exploitation of the emulsions. Abstract : All-aqueous emulsions are conventionally formed at bulk scale by mild shaking of aqueous two-phase systems. They can be used to carry out reactions both in droplets (compartmentalized) and on droplet surfaces in conditions free of synthetic surfactants and organic solvents. The use of all-aqueous emulsions for extractive bioconversion is a routine application; however, these emulsions hold many more promises. A renowned, rapidly evolving application is bio-microgel synthesis through biopolymer crosslinking within the emulsion internal phase. When polyelectrolyte crosslinking is achieved at the interface rather than in droplets, microcapsules can be formed, and when in situ colloidal particle generation at the droplet surface is obtained, colloidosomes are produced. The use of microfluidics to control the formation of all-aqueous emulsions offers many advantages in reactions monitoring and partitioning of reactants.